5-[(2-Chloro-4-nitroanilino)methylidene]-2,2-dimethyl-1,3-dioxane-4,6-dione - Xian-Qiu Lan (Acta Crystallographica Section E, 2011)
In the title compound, C13H11ClN2O6, the dihedral angles between the benzene ring and the aminomethylene unit and between the aminomethylene group and the dioxane ring are 8.19 (14) and 1.39 (17)°, respectively. The dioxane ring has a half-boat conformation, in which the C atom between the dioxane O atoms is 0.662 (4)Å out of the plane through the remaining ring atoms. Intramolecular N—H...O and N—H...Cl interactions occur.